Bryostatin Activates CAR T-Cell Antigen-Non-Specific Killing (CTAK), and CAR-T NK-Like Killing for Pre-B ALL, While Blocking Cytolysis of a Burkitt Lymphoma Cell Line - Wang, Lingyan; Zhang, Yue; Anderson, Eden; Lamble, Adam; Orentas, Rimas J. (Frontiers in Immunology, 2022)
The advent of CAR-T cell therapy has changed the face of clinical care for relapsed and refractory pre-B-acute lymphocytic leukemia (B-ALL) and lymphoma. Although curative responses are reported, long-term cures remain below 50%. Different CAR T-cell leukemia targets appear to have different mechanisms of CAR-T escape. For CD22, therapeutic evasion is linked to down-modulation of the number CD22 proteins expressed on the extracellular aspect of the leukemia cell plasma membrane. Recently, pharmacologic agents known to induce cellular differentiation or epigenetic modification of leukemia have been shown to impact CD22 and CD19 expression levels on B-ALL, and thereby increase sensitivity to CAR-T mediated cytolysis. We explored the impact of epigenetic modifiers and differentiation agents on leukemia cell lines of B cell origin, as well as normal B cells. We confirmed the activity of bryostatin to increase CD22 expression on model cell lines. However, bryostatin does not change CD22 levels on normal B cells. Furthermore, bryostatin inhibited CAR-T mediated cytolysis of the Raji Burkitt lymphoma cell line. Bryostatin increased the cytolysis by CD22 CAR-T for B-ALL cell lines by at least three mechanisms: 1) the previously reported increase in CD22 target cell numbers on the cell surface, 2) the induction of NK ligands, and 3) the induction of ligands that sensitize leukemia cells to activated T cell antigen-non-specific killing. The opposite effect was seen for Burkitt lymphoma, which arises from a more mature B cell lineage. These findings should caution investigators against a universal application of agents shown to increased killing of leukemia target cells by CAR-T in a specific disease class, and highlights that activation of non-CAR-mediated killing by activated T cells may play a significant role in the control of disease. We have termed the killing of leukemia targets, by a set of cell-surface receptors that does not overlap with NK-like killing “CTAK,” CAR-T Cell antigen-non-specific killing.